Treatment‐related risk factors for inhibitor development in non‐severe hemophilia A after 50 cumulative exposure days: A case‐control study. (19th July 2021) - Abdi, Amal; Eckhardt, Corien L.; van Velzen, Alice S.; Vuong, Caroline; Coppens, Michiel; Castaman, Giancarlo; Hart, Dan P.; Hermans, Cedric; Laros‐van Gorkom, Britta; Leebeek, Frank W. G.; Mancuso, Maria Elisa; Mazzucconi, Maria G.; et al.
Abstract: Background: Non‐severe hemophilia A patients have a life‐long inhibitor risk. Yet, no studies have analyzed risk factors for inhibitor development after 50 factor VIII (FVIII) exposure days (EDs). Objectives: This case‐control study investigated treatment‐related risk factors for inhibitor development in non‐severe hemophilia A and assessed whether these risk factors were different for early versus late inhibitor development. Patients/Methods: Non‐severe hemophilia A patients (FVIII:C 2%–40%) were selected from the INSIGHT study. Inhibitor‐positive patients were defined as early (<50 EDs) or late (>50EDs) cases and matched to 1–4 inhibitor‐negative controls by year of birth, cumulative number of EDs, and center/country. We investigated treatment intensity during the last 10 EDs prior to inhibitor development. Intensive treatment was defined as: surgery, peak treatment (10 consecutive EDs), and high mean FVIII dose (>45 IU/kg/ED). Odds ratios (OR) were calculated by logistic regression. Results: Of 2709 patients, we analyzed 63 early and 26 late cases and 195 and 71 respectively matched controls. Peak treatment was associated with early and late inhibitor risk (crude OR 1.8, 95% confidence interval [CI] 1.0–3.4; 4.0, 95%CI 1.1–14.3). This association was slightly less pronounced after adjustment for mean FVIII dose. High mean FVIII dose was also associated with early and late inhibitor risk (crude OR 2.8, 95%CI 1.5–5.1; 4.5, 95%CI 1.2–16.6). Surgery increased inhibitor risk for early cases. This was less pronounced for late cases. Conclusions: Our findings suggest that intensive FVIII treatment remains a risk factor for inhibitor development in non‐severe hemophilia A after more than 50 EDs. Therefore, persistent caution is required throughout the life‐time treatment course.